Cis- and trans-regulations of pre-mRNA splicing by RNA editing enzymes influence cancer development - Sze Jing Tang (Nature Portfolio, 2020)
RNA editing and RNA splicing are involved in tumorigenesis. Here the authors report crosstalk between RNA editing and splicing by identifying ADAR1/2-dependent splicing events in esophageal squamous carcinoma cells.